Assessment of Interferon-γ Levels and Leishmanin Skin Test Results in Persons Recovered for Leishmaniasis - Alimohammadian, Mohammad H. (The American Society of Tropical Medicine and Hygiene, 2012)
Patients who recover from leishmaniasis usually show development of strong immunity and induction of interferon-γ (IFN-γ) and delayed type hypersensitivity. In a randomized trial, we analyzed the IFN-γ response by using a Quantiferon–Leishmania assay against three Leishmania peptide antigens and compared it with results of the leishmanin skin test (LST) in persons residing in areas in Iran to which zoonotic cutaneous leishmaniasis (ZCL, 181 persons), anthroponotic cutaneous leishmaniasis (ACL, 104 persons), and zoonotic visceral leishmaniasis (ZVL, 67 persons) are endemic. The percentage of persons with an IFN-γ-positive response (> 0.2 IU/mL) to three antigens and the mean concentration of IFN-γ induced by the antigens were higher for persons from areas endemic for ZVL than for persons from areas endemic for ZCL and ACL. The percentage of persons with LST-positive results (≥ 5 mm indurations) was 99%, 94%, and 70% for areas with ZCL, ACL, and ZVL, respectively. Our data indicate that the LST is significantly more sensitive than IFN-γ levels in persons who have been cured of cutaneous leishmaniasis than in persons who have been cured of ZVL.